IMPLEMENTASI KECERDASAN MAJEMUK DALAM PEMBELAJARAN - Gusti Handayani (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2024)
Multiple intelligence is a theory introduced by Howard Gardner that aims to optimize the intelligence possessed by each individual (student) in terms of achieving certain competencies. There are nine types of multiple intelligence, which are linguistic intelligence, logical mathematical intelligence, visual-spatial intelligence, musical intelligence, kinesthetic intelligence, interpersonal intelligence, intrapersonal intelligence, naturalist intelligence and existential intelligence.